2013
DOI: 10.4236/ajps.2013.410241
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characteristics and QTL Mapping Associated with the Lipid Content of High-Lipid Rice

Abstract: This study was conducted to examine the physicochemical characteristics and perform QTL mapping of genetic factors associated with the lipid content of rice. A rice strain with a high lipid content, "P31-2-2-2-B-B", was developed from mutants of "Dongjin" created by T-DNA insertion. The lipid content of "P31-2-2-2-B-B" brown rice was 4.42% whereas that of the donor cultivar "Dongjin" was 2.56%. The total fatty acid content of the high-lipid mutant brown rice was 7.82% and that of "Dongjin" was 3.43%. The unsat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
2
1
Order By: Relevance
“…Other studies have found QTLs associated with protein and lipid content on chromosomes 5 and 7, respectively. The three QTLs related to protein and lipid content was located at different positions from those reported in previous studies [13] [14]. These differences likely resulted from the difference in genetic stock.…”
Section: Qtl Analysiscontrasting
confidence: 54%
“…Other studies have found QTLs associated with protein and lipid content on chromosomes 5 and 7, respectively. The three QTLs related to protein and lipid content was located at different positions from those reported in previous studies [13] [14]. These differences likely resulted from the difference in genetic stock.…”
Section: Qtl Analysiscontrasting
confidence: 54%
“…The QTLs for protein content were detected commonly on chromosomes 3, 6, and 7 [68]. Also the QTLs for lipid content were commonly detected on chromosomes 5, 6, and 7 [69]. In spite of many results, several new QTLs related to amylose and proteins were detected on chromosomes 11 and 2, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Among these loci, qFC-5 on chromosome 5 was the QTL with the largest effect, explaining 12.9% of the phenotypic variance and showing an additive effect of 0.091% [8]. QTL related to rice lipid content (RLC) with 2.37 of LOD score was identified on chromosome 5 from the high lipid mutant line derived from “Dongjin” by T-DNA insertion [9]. …”
Section: Introductionmentioning
confidence: 99%